Hematopoietic stem cell transplantation for sickle cell disease: Progress and challenges. Issue 9 (24th May 2018) - Hulbert, Monica L.; Shenoy, Shalini
Abstract: Sickle cell disease (SCD) presents challenges to hematopoietic stem cell transplantation (HSCT), including donor availability and morbidity with age/disease severity. However, severe SCD causes irreversible organ damage that HSCT can mitigate. This benefit must be balanced against preparative regimen toxicity, graft‐versus‐host disease, and mortality risk. We review efforts to balance HSCT complications with the promise of cure, and knowledge gaps that warrant further investigation. We highlight the burden of SCD, HSCT risks and benefits, and SCD families' approach to this balance. We emphasize the necessity for information exchange to ensure a joint decision‐making process between providers and patients.